CONSUMER BEHAVIOUR IN PRIVATE BANKING - van der Merwe, Carol-Ann (My University, 2011)
Appropriately segmented target markets guide effective business strategies. Most South African private banks use wealth to segment clients, for example, into high net worth and high income markets. This ignores the differences in and similarities of clients‟ motivations, expected benefits, attitudes, perceptions and product usage. The purpose of this research was to investigate any differences in the consumer behaviour of high net worth and high income individuals. Factor analysis was used to reduce 28 variables into four factors reflecting consumer behaviour patterns in private banking: Involved Decision Making, Traditional Private Banking, Valued Bank Relationships and Personal Interaction Trade-off. T-testing was done to determine any significant differences. The findings revealed that no significant difference existed between high net worth and high income individuals. The implication is that in addition to using wealth as a segmentation criterion, private banks will have to incorporate consumer behaviour criteria to improve their market segmentation models
MBA thesis - WBS
Keywords: Consumer behaviour; Banks and banking; Private banking